Acute and chronic eosinophilic pneumonia: an overview - Carbone, Roberto G.; Puppo, Francesco; Mattar, Eduardo; Roden, Anja C.; Hirani, Nikhil (Frontiers in Medicine, 2024)
Acute and chronic eosinophilic pneumonia (AEP and CEP) include a group of rare interstitial lung diseases characterized by peripheral blood eosinophilia, increased eosinophils in bronchoalveolar lavage fluid, or eosinophilic infiltration of lung parenchyma. AEP is characterized by rapid onset, fast response to steroid treatment and no relapse. CEP is characterized by marked tissue and peripheral blood eosinophilia, rapid response to steroid therapy and tendency to disease recurrence. In addition, we briefly describe other eosinophilic lung diseases that must be considered in differential diagnosis of AEP and CEP. Eosinophilic pneumonias may be idiopathic or due to known causes such as medications or environmental exposure. At variance with previous reviews on this topic, a particular look in this overview was directed at pathological findings and radiological patterns.